Endotheliopathy Is Associated With a 24-Hour Fibrinolysis Phenotype Described by Low TEG Lysis and High d-Dimer After Trauma: A Secondary Analysis of the PROPPR Study. Issue 1 (26th March 2022) - Richter, Robert P.; Joiner, Danielle M.; Griffin, Russell L.; Jansen, Jan O.; Kerby, Jeffrey D.; Wade, Charles E.; Holcomb, John B.; Cardenas, Jessica C.; Richter, Jillian R.
Abstract : Objectives: Determine associations between biomarkers of endotheliopathy, 24-hour fibrinolysis phenotypes and clinical outcomes after trauma. Background: The vascular endothelium is a critical regulator of hemostasis and organ function. The relationship between markers of endotheliopathy and fibrinolysis following trauma has not been evaluated. Methods: We performed a secondary analysis of prospectively collected biomarker data in the Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) randomized controlled trial. We stratified subjects by 24-hour thromboelastography (TEG) percent clot lysis (LY30) and plasma d -dimer (DD) levels and evaluated differences in endotheliopathy biomarkers and clinical outcomes between subjects with one of four 24-hour fibrinolysis phenotypes: LY30 0.9% to 2.9% (LY30norm ), LY30 > 2.9% (LY30high ), LY30 < 0.9% and low DD (LY30low +DDlow ), and LY30 < 0.9% and high DD (LY30low +DDhigh ). Results: The analysis included 168 subjects with LY30norm, 32 with LY30high, 147 with LY30low +DDlow, and 124 with LY30low +DDhigh . LY30low +DDhigh subjects had greater injury severity and a higher incidence of severe head injury, multiorgan failure (MOF), and mortality than the other phenotypes. All endotheliopathy biomarkers were significantly higher in the LY30low +DDhigh phenotype. Adjusting for injury severity, mechanism, and head trauma, 24-hour angiopoietin-2 and soluble thrombomodulin were independently associated with the LY30low +DDhigh phenotype. Both endothelial biomarkers were discriminating for MOF. Subjects with thrombomodulin level >9.5 ng/mL and angiopoietin-2 level >3.6 ng/mL accounted for 64% of subjects who developed MOF. Conclusions: In a multicenter trauma cohort, subjects with a fibrinolysis phenotype characterized by low TEG lysis and elevated DD 24 hours after injury have significantly worse endotheliopathy and clinical outcomes. Our findings support mechanistic evaluations of the role of the endothelium in fibrinolysis dysregulation that may drive late-stage organ injury. Abstract : Mini-abstract: This retrospective study evaluated the associations between endotheliopathy biomarkers, 24-hour fibrinolysis phenotypes and clinical outcomes after trauma. Subjects with a fibrinolysis phenotype characterized by low TEG lysis and elevated d -dimer levels 24 hours after injury had significantly worse endotheliopathy and clinical outcomes. Circulating levels of angiopoietin-2 and thrombomodulin were identified as endothelial biomarkers with potential utility for discriminating multiorgan failure. Supplemental Digital Content is available in the text.